Assessing Safety Climate Dimensions in the Textile Industry: A Correlational Study Using the NOSACQ-50 Framework - Rici Riansyah; Tyas Lilia Wardani; Isna Qadrijati; Jihan Faradisha; Afrian Eskartya Harjono; Rizqy Kartika Sari; Rachmawati Prihantina Fauzi; Reni Wijayanti (Journal of Health and Nutrition Research, 2026)
The manufacturing sector, particularly the textile industry, faces high occupational accident risks due to inadequate Occupational Health and Safety (OHS) culture. This study evaluates the safety climate in the textile industry and examines the relationship between the seven dimensions of the NOSACQ-50 framework and the overall safety climate. Utilizing a descriptive quantitative, cross-sectional approach, data was collected from 100 purposively sampled workers through the NOSACQ-50 questionnaire, direct workplace observations, and interviews. Data was analyzed using univariate and bivariate (Spearman's rank) methods. Univariate results indicated a "good" overall safety climate with an average score of 3.06 across all dimensions. However, the dimension concerning OHS communication and coworker competence scored the lowest (2.95), identifying a specific area for improvement. Bivariate analysis revealed highly significant correlations between specific dimensions and the overall safety climate. Notably, employee commitment to OHS components demonstrated a very strong relationship (r = 0.783). Furthermore, employee safety priorities and workplace hazard control also exhibited a very strong and significant correlation with the safety climate (r = 0.787). In conclusion, while the general safety climate is good, prioritizing improvements in OHS communication is necessary. Fostering employee commitment and safety priorities plays a crucial role in maintaining a positive safety climate.